Analisis Wacana Pencalonan Presiden dan Wakil Presiden Non Partai Politik di Indonesia dalam Kerangka Negara Demokrasi - Aprista Ristyawati (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2021)
Abstract This study aims to analyze the discourse on the nomination of President and Vice President of non-political parties in Indonesia within the framework of a democratic state. The approach method used in this research is normative juridical and descriptive analytical, namely describing the object that is the subject of the problem, from the description an analysis is taken that is adapted to existing legal theories and puts the law as a building system of norms. The results of this study indicate that the mechanism for nominating the President and Vice President has indeed shown democratic values but only accommodates the nomination route through political parties so that it closes the rights of some citizens who want to run through non-political parties. If the current regulations are applied, so that the mechanism for nominating the President and Vice President in Indonesia is more effective, the criteria for candidate quality must be further improved. The discourse of Presidential and Vice-Presidential Candidates for Non-Political Parties in Indonesia has advantages, namely reducing political oligarchy, presidential system is more effective, providing opportunities for potential candidates in small political parties and non-political parties, recruitment system and regeneration patterns are more loyal and quality. Weaknesses include the presence of an envoy Number 56/PUU-VI/2008 of the Constitutional Court of the Republic of Indonesia, the prevailing regulations still accommodate the constitutional rights of citizens, weakening the function and role of Political Parties, the potential for dismissal of the President and Vice President by the proposal of the House of Representatives. Keywords: Candidate for President and Vice President, Non-Political Party, Democracy Abstrak Penelitian ini bertujuan untuk menganalisis wacana pencalonan Presiden dan Wakil Presiden non Partai Politik di Indonesia dalam kerangka negara demokrasi. Metode pendekatan yang digunakan dalam penelitian ini adalah yuridis normatif dan bersifat deskriptif analitis yaitu menggambarkan objek yang menjadi pokok permasalahan, dari penggambaran tersebut diambil suatu analisa yang disesuaikan dengan teori-teori hukum yang ada dan meletakan hukum sebagai sebuah bangunan sistem norma. Hasil penelitian ini menunjukkan bahwa mekanisme pencalonan Presiden dan Wakil Presiden memang sudah menunjukan nilai demokrasi namun hanya mengakomodir jalur pencalonan melalui partai politik sehingga menutup hak sebagian warga negara yang ingin mencalonkan diri melalui jalur non-partai politik. apabila memang aturan yang ada saat ini yang diberlakukan, agar mekanisme pencalonan Presiden dan Wakil Presiden di Indonesia lebih efektif maka kriteria kualitas kandidat harus lebih ditingkatkan. Wacana Pencalonan Presiden dan Wakil Presiden Non Partai Politik di Indonesia memiliki kelebihan yaitu mengurangi oligarki politik, sistem presidensiil lebih efektif, memberikan peluang bagi kandidat berpotensi pada partai politik kecil maupun non partai politik, sistem rekrutmen dan pola kaderisasi lebih loyal dan berkualitas. Kelemahannya antara lain adanya utusannya Nomor 56/PUU-VI/2008 Mahkamah Konstitusi Republik Indonesia, regulasi yang berlaku tetap mengakomodir hak konstitusional Warga Negara, melemahkan pungsi dan peran Partai Politik, adanya potensi pemberhentian Presiden dan Wakil Presiden oleh usulan Dewan Perwakilan Rakyat. Kata Kunci : Pencalonan Presiden dan Wakil Presiden, Non Partai Politik, Demokrasi